2003
DOI: 10.1159/000073400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Presence of Demarcated Opacities and Hypoplasia in Permanent Teeth and Caries in Their Primary Predecessors

Abstract: Objective: To investigate the relationship between the presence of demarcated opacities and hypoplasia on permanent teeth and the caries status of the primary predecessor teeth in a cohort of Chinese children. Methods: The study sample consisted of 250 children living in a non-fluoridated area in Southern China whose caries status of primary teeth at the age of 3–6 years had been recorded annually in a previous study. A follow-up examination of their permanent teeth was conducted when they were about 12 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
3
18
0
9
Order By: Relevance
“…Demarcated opacities in the permanent teeth have also been reported to be twice more likely if caries had been present in the primary precursor [Lo et al, 2003;Broadbent et al, 2005;Arrow, 2009]. Thus, it is probable that the LR-VLBW adolescents with demarcated opacities could have had a carious primary precursor tooth that was not possible to assess in this study.…”
Section: Dental Caries In Vlbw Childrenmentioning
confidence: 84%
See 1 more Smart Citation
“…Demarcated opacities in the permanent teeth have also been reported to be twice more likely if caries had been present in the primary precursor [Lo et al, 2003;Broadbent et al, 2005;Arrow, 2009]. Thus, it is probable that the LR-VLBW adolescents with demarcated opacities could have had a carious primary precursor tooth that was not possible to assess in this study.…”
Section: Dental Caries In Vlbw Childrenmentioning
confidence: 84%
“…Demarcated opacities in early erupting permanent teeth (incisors and first molars) are associated with neonatal risk factors [Jalevik et al, 2001;Arrow, 2009] while diffuse opacities are associated with infant fluoride [Pendrys, 1999] and amoxicillin exposure [Hong et al, 2005]. Demarcated opacities in permanent teeth have been associated with caries in the precursor primary teeth [Lo et al, 2003;Broadbent et al, 2005;Arrow, 2009].…”
mentioning
confidence: 99%
“…For example, dental caries in a primary tooth has been found to be an aetiological factor for the presence of demarcated opacities in their permanent successors [Lo et al, 2003]. It has also been reported that children who manifest rapid growth tend to have their teeth erupt earlier than normal children [Soliman et al, 2012].…”
Section: Infant Growth and Ddementioning
confidence: 99%
“…What is clear is that the status of the primary dentition can predict caries in permanent teeth [8][9][10] and therefore most of the recommendations are either: to intervene early or prevent carious lesions; carry out caries risk assessments; or specific dietary recommendations. For example, recommendations include toothbrushing with fluoride toothpaste (even for children under 2 years old, with a smear size amount of fluoride) and oral health promotion programmes for parents and continued postnatal care -a recommendation based on evidence from nonanalytical studies (case reports or case series) that in fact represents evidence from clinical trials.…”
Section: Commentarymentioning
confidence: 99%